2020
DOI: 10.22146/ijg.49366
|View full text |Cite
|
Sign up to set email alerts
|

The Spatiotemporal Analysis of Dengue Fever in Purwosari District, Gunungkidul Regency, Indonesia

Abstract: From 2014 to 2016, the number of prevalence of Dengue Hemorrhagic Fever (DHF) and deaths associated with DHF in Indonesia increased. DHF fatal cases were also reported from three administrative units in the Special Region of Yogyakarta, namely Bantul Regency, Gunungkidul Regency, and Yogyakarta City. Two related deaths in Purwosari, a district in Gunungkidul, raised the status of DHF to an outbreak. This study was designed to characterize the spread pattern of DHF in its endemic areas in Purwosari District usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Findings of a study conducted in Indonesia, have shown that an increase in the dengue fever cases with 1% decrease in relative humidity (Husnina, Clements, & Wangdi, 2019). On the contrary, an Indonesian study conducted during 2011 -2017 period revealed that higher number of DHF cases are reported in areas with increased humidity (Riyanto et al, 2020). This is also supported by the evidence from a study conducted in Thailand which revealed that the maximum incidence of DHF cases occur at mean humidity of >80% and minimum humidity >62% (Campbell, 2014).…”
Section: Impact Of Humidity On Denguementioning
confidence: 85%
See 1 more Smart Citation
“…Findings of a study conducted in Indonesia, have shown that an increase in the dengue fever cases with 1% decrease in relative humidity (Husnina, Clements, & Wangdi, 2019). On the contrary, an Indonesian study conducted during 2011 -2017 period revealed that higher number of DHF cases are reported in areas with increased humidity (Riyanto et al, 2020). This is also supported by the evidence from a study conducted in Thailand which revealed that the maximum incidence of DHF cases occur at mean humidity of >80% and minimum humidity >62% (Campbell, 2014).…”
Section: Impact Of Humidity On Denguementioning
confidence: 85%
“…Muurlink et al,2018 have revealed that the best predictors of an dengue outbreak are the number of rainy days in the preceding two months (Muurlink, Stephenson, Islam, & Taylor-Robinson, 2018). According to studies conducted in Indonesia and India, there is a significant association between cumulative rainfall (Ali et al, 2020;Arcari & Tapper, 2017;Arcari, Tapper, & Pfueller, 2007;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, Murhekar, et al, 2020;Riyanto et al, 2020;Roy et al, 2018;Salamah et al, 2012). A significant weak correlation between higher rainfall and incidence of DHF cases has been found in two studies conducted in Indonesia (Haryanto, 2016); (Salim & Syairaji, 2020).…”
Section: Impact Of Rainfall On Denguementioning
confidence: 99%
“…The information on the prospective spread of the Aedes aegypti mosquito in the Pekanbaru City region is still limited and incomplete, particularly when it comes to the environmental dispersion of the Aedes aegypti mosquito, which is important for early prevention . One strategy to combat the problem of dengue haemorrhagic fever is to eliminate or limit the presence of the Aedes aegypti mosquito (Riyanto et al, 2020). The presence of bias is generally one of the disadvantages of utilizing the approach in a problem; however, in the environmental needs of the Aedes aegypti mosquito, a class criteria value limit is given to eliminate this bias (Maula et al, 2018;Majid et al, 2019).…”
Section: Introductionmentioning
confidence: 99%